Review of cost estimation: methods and models for aerospace composite manufacturing. (2nd January 2016) - Hueber, Ch.; Horejsi, K.; Schledjewski, R.
Abstract: This review aims to provide an overview to the extensive field of cost estimation for aerospace composite production, describing the basic methods of how to perform cost estimation and introducing some of the existing models. While some might claim for more existing estimation methods this review, however, recommends the classification into only the three primary methods: analogous, parametric, and bottom-up cost estimation. Furthermore, a selection of the existing cost estimation models for the aerospace composite manufacturing will also be presented and detailed here in this paper. Models are considered to be structures embedding one more of the basic estimation methods in an attempt to enhance or combine their different strengths. This paper also focuses on some of the main issues encountered when engaging in cost estimation. Abstract :